Immunoregulatory Effect Of Ethanolic Extract Propolis (Eep) From Geniotrigona thoracica sp. On The Formation Of THP-1 Derived Macrophage Foam Cells - Mohd Suib, Muhammad Syamil (2018)
Propolis is a complex resinous substances collected by bees from buds and exudates of plants that has been reported to demonstrate various therapeutic potential. The usage of natural product such as propolis has been used for treatment of various chronic diseases which includes atherosclerosis. Atherosclerosis is a chronic inflammatory disease involving the formation of monocyte derived macrophage foam cells in arteries, which play a major role in atherogenesis. Studies showed that propolis produced by honeybees may inhibit atherosclerosis but there is no studies that have been performed using propolis produced by Indo-Malayan stingless bees.